Autonomous learning for facial identification (2018)
Machine learning driven solutions are being seek after more than ever before. Presenting a way to solve complicated business problems and aid in the research of countless fields. The modern software developers face the challenge to design and implement functional and practical solutions using the potential of machine learning. To accomplished this, it will be necessary to find practical and efficient ways to harness and collect data and information. In this paper, we test the feasibility of an application that crowdsources and processes the data required to train a machine learning model. For this, we will create a facial identification application that uses this method, which I will refer as autonomous learning